Utilization of Documentary Video Learning Media in Improving Students' Learning Motivation in The History Lesson of Grade XI TKJ at State Vocational High School 1 Banawa - Shivani, Nifla Juniar; Nugroho, Fajar; Iskandar; Mutawakkil (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to analyze the use of documentary video-based learning media to increase student learning motivation in history in grade XI TKJ SMKN 1 Banawa. The background of this study is based on the low motivation of students in learning history when only using conventional methods, so a more engaging, contextual, and appropriate media is needed for students' characteristics. This study used a qualitative approach with descriptive methods. Data were collected through observation, interviews, and documentation over seven meetings, then analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the use of documentary video can increase student learning motivation. This was evident in increased student enthusiasm during learning, active participation in discussions, courage to ask questions, and willingness to summarize the video content. Teachers also stated that students became more focused, understood historical events more easily, and did not get bored easily. Challenges encountered included limited technical facilities such as projectors and speakers, limited personal devices for re-watching videos, and some students' unfamiliarity with learning through audiovisual media.